2019
DOI: 10.4018/978-1-5225-3267-5.ch009
|View full text |Cite
|
Sign up to set email alerts
|

Role of Diet, Functional Foods, and Nutraceuticals in Brain Disorders

Abstract: This chapter presents an overview of various complementary nutritional approaches for the management of brain disorders. Numerous epidemiological studies emphasize the growing burden of brain disorders worldwide. Due to the complex pathophysiology, lack of precise diagnostic and therapeutic options, there is growing need to have alternative approaches. One important strategy for the prevention and treatment of brain impairment is based on dietary supplements, functional foods, and nutraceuticals. The current c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…The current trends and demands for a healthier diet include consuming more vegetables and fruits on a daily basis [ 31 ]. Worldwide national health systems recommend such improvements in diets in order to help counteract the high prevalence of metabolic-related diseases, such as obesity, diabetes, or hyperglycemia [ 32 , 33 , 34 ], along with economic and social considerations [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The current trends and demands for a healthier diet include consuming more vegetables and fruits on a daily basis [ 31 ]. Worldwide national health systems recommend such improvements in diets in order to help counteract the high prevalence of metabolic-related diseases, such as obesity, diabetes, or hyperglycemia [ 32 , 33 , 34 ], along with economic and social considerations [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since one of the main points of intervention for a healthy lifestyle is diet, global health recommendations are always encouraging the message of eating a minimum of five portions of fruits and vegetables daily [3,4]. Vegetables are not only a natural source of amino acids and minerals, but also of phytochemicals [5].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, during the last few years, the prevention and management of non‐communicable diseases, including diabetes and obesity, are being approached with nutritional interventions . In relation to this, vegetables and fruits are the main sources of phytochemicals in our diets and, around the world, the recommendation for the general population is to eat at least five portions of fruits and vegetables per day in order to reduce the risk of many diseases and to maintain physical and mental wellness …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] In relation to this, vegetables and fruits are the main sources of phytochemicals in our diets and, around the world, the recommendation for the general population is to eat at least five portions of fruits and vegetables per day in order to reduce the risk of many diseases and to maintain physical and mental wellness. 5,6 Particularly rich in bioactive compounds are the vegetables of the Brassicaceae family, not only for their nutritional profile but also for the presence of health-promoters such as glucosinolates (GLSs), phenolic acids and flavonoids, vitamin C, and minerals. 7 Broccoli (both as a mature vegetable or as sprouts) has been one of the main subjects of consumer and research interest for the last 20 years, since diverse studies have shown that its regular consumption decreases the risk of colon and lung cancer, among other chronic health conditions.…”
Section: Introductionmentioning
confidence: 99%